Young generation and environmental friendly awareness: does it the impact of green advertising? - Herman, Lalu Edy; Udayana, Ida Bagus Nyoman; Farida, Naili (Business: Theory and Practice, 2021)
The environmental issues nowadays have make consumers becoming more selective in selecting products and brands going to use. The purpose of this study is to investigate the effect of green advertising on green purchase intentions mediated by green attitude awareness in the young generation. Young generation has strong curiosity and has easier access on getting products information, so this research focuses deeper on examining how much green advertising, green knowledge, and eco-label information affect the awareness on green attitude which later influences green intention to purchase. This research used primary data obtained from questionnaires distributed directly to 150 undergraduate students of universities in Indonesia. We used Structural Equation Modeling (SEM) for verifying hypothesis and AMOS 20 software for getting empirical results of 16 items questions representing indicator of 4 variables. The result showed that green advertising and green knowledge were able to form the awareness on environmental friendly. Although eco-label information did not influence the awareness on green attitude, it influenced the green purchase intention directly.